The management of firm specific resources as a source of competitive advantage - Burton-Taylor, Sarah (Cranfield University, 2004)
This study is about helping managers identify and enhance the idiosyncratic firm resources required for delivering superior perceived use value to customers. Specifically, the research has focused on the organisational knowledge required for routinised service delivery, and has operationalised this organisational knowledge as activities. Project 1 was a comparative study involving observation and interviews in two similar but differentially performing financial services organisations in order to identify the activities involved in service delivery and the differences between the two operations. Project 2 identified customers’ perceptions of value through customer interviews, and then mapped the links between these and the service delivery activities identified in Project 1. Project 3 involved a clinical inquiry intervention aiming to encourage and leverage the firm specific resource of inter-team coordination to enhance the delivery of customer value. The research has confirmed the role of firm specific resources as a source of competitive advantage, and has demonstrated a link with customers’ dimensions of perceived use value. In this study, effective inter-team coordination is identified as the firm specific strategic resource that appears to enable effective service delivery as perceived by customers, through the sharing of knowledge and interpretations, and the development of service process innovation. Many of these coordination activities are discretionary rather than prescribed, with implications for management practice. From this research, a framework has been developed for considering and managing firm specific sources of advantage at the detailed operational level. This is a micro level approach that makes specific links between the customer experience and internal activities, through identifying internal and external competitiveness factors, mapping the ‘inside-outside’ connections, and achieving alignment between internal activities and customer perceptions of value.
Keywords: Customer service; Service delivery; Competitive advantage; Perceived use value